The structural phase transition process of free-standing monoclinic vanadium dioxide micron-sized rods: temperature-dependent Raman study. Issue 101 (30th September 2015) - Zhang, Huafang; Li, Quanjun; Shen, Pengfei; Dong, Qing; Liu, Bo; Liu, Ran; cui, Tian; Liu, Bingbing
Abstract : Micro-sized rods show a lower phase transition temperature than nano-sized rods, and this is interpreted on the basis of nucleating defects. Abstract : We investigated the temperature-driven structural phase transition (SPT) process of free-standing monoclinic vanadium dioxide (VO2 (M)) micron-sized rods by Raman spectroscopy. With increasing temperature, the phase transition sequence goes monoclinic M1 → monoclinic M1 /monoclinic M2 /rutile (R) → monoclinic M2 /R → R. The fully metallic R phase is reached at 50 °C, which is 7 °C lower than the value of nanoparticles in our study and 18 °C lower than the value of early reports on VO2 (M) bulk materials. The intermediate M2 phase, which plays a critical role in the monoclinic to rutile transition (MRT), was clearly observed in both heating and cooling process of the micron-sized free-standing VO2 (M) rods. We suggest that the existence of nucleating defects in our samples, which have an important effect on the nucleation of the R phase, are responsible for the reduction of the phase transition temperature and the appearance of the M2 phase. This supplies a possible way to expand the practical applications of one dimensional VO2 materials.